2021
DOI: 10.1038/s41433-021-01541-x
|View full text |Cite
|
Sign up to set email alerts
|

The performance of iPad-based noise-field perimeter versus Humphrey Field Analyser in detecting glaucomatous visual field loss

Abstract: Background To conduct a preliminary evaluation of the feasibility of visual field fast (VFF), a free iPad-based noise-field perimeter, in detecting glaucomatous scotomas versus the clinical-standard Humphrey visual field (HVF) test. VFF confronts subjects with a screen of flickering stimulus, allowing the immediate perception of scotomas. Methods This was a cross-sectional observational study of 66 glaucoma patients (66 eyes) and 30 healthy controls (30 eyes). All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Their publication dates ranged between 2005 and 2021. The majority were cross-sectional clinical-based studies and were conducted in USA, 29,37,40,41 India, 27,30 UK, 26,31 Australia, 33,36 Singapore, 24 Greece, 34 Nepal, 35 Denmark, 38 and Philippines. 39 Two home-based longitudinal studies were conducted in UK 25 and Australia 28 , while one was a multicenter clinical-based study conducted in UK and India.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Their publication dates ranged between 2005 and 2021. The majority were cross-sectional clinical-based studies and were conducted in USA, 29,37,40,41 India, 27,30 UK, 26,31 Australia, 33,36 Singapore, 24 Greece, 34 Nepal, 35 Denmark, 38 and Philippines. 39 Two home-based longitudinal studies were conducted in UK 25 and Australia 28 , while one was a multicenter clinical-based study conducted in UK and India.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…39 Two home-based longitudinal studies were conducted in UK 25 and Australia 28 , while one was a multicenter clinical-based study conducted in UK and India. 32 Participants were recruited from clinics and had detailed ophthalmological examinations, except in 5 studies 24,32,34,40,41 where examinations were not reported. Three studies 25,28,32 included patients with glaucoma or ocular hypertension, 11 studies 24,26,27,[29][30][31]33,[36][37][38]41 included glaucoma patients and healthy controls, 3 studies 35,39,40 also included patients with other diagnosis, and 1 study 34 did not specify participant diagnosis.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations